Enhancing Adaptive Capacity of Indian Agriculture to Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Presentation by Pramod Aggarwal (Indian Agricultural Research Institute). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya